Outsourcing vs. employee leasing – practical issues and forms of violations - Jurkiewicz, Monika (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
This study aims to show the reader the differences between employee outsourcing and employee leasing, focusing on the practical aspects of the differences between these institutions, while also showing what the potential consequences associated with the improper use of these solutions may be. Thus, the purpose of this text is to show readers that the way to effective and efficient use of outsourcing or employee leasing is to have a good understanding of the differences between them. In this way, entrepreneurs can apply these solutions effectively gaining not only cost optimization, but also speed and flexibility in obtaining resources to execute the acquired contracts.